Navigating Against Salafi-Wahabi Expansion in Malaysia: The Role of State and Society - Abdullah, Kamarulnizam (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2022)
This article argues that Salafi-Wahhabism’s political ideology has major effects on Malaysia’s socio-political orders. It also argues that the levels of resilience to the Salafi-Wahabi expansion are varied between state and society. At the level of society, resilience is weakened by multiple layers of grievances, which produced various effects brought by stages of reformist movements and terrors of neo-Salafi groups. The crucial indicator is its changing characteristics from being accommodative to a defensive one. The increasing tendency of Muslims embracing Salafi-Wahabism is the result of years of indoctrination, transnational Islamist networking, an external source of religious-funded activities, and the politicization of Islam. Yet this has been outweighed by the state’s resilience. Several attributes could explain the state’s ability to resist internal and external sources of radical ideologies, among others, long experience with terror threats, the state’s defined Islam, strong control on religious affairs, and the law enforcement that existed since the colonial periods.